Defining laboratory medicine, or squaring the circle? - Watine, Joseph (Array, 2021)
In the August 2020 issue of Clinical Chemistry and Laboratory Medicine, Giuseppe Lippi and Mario Plebani proposed a definition of laboratory medicine, which ends with this sentence: "The results of these measurements are translated into actionable information for improving the care and/or maintaining the wellness of both a single individual and an entire population". Nevertheless, the selfishness of individuals may, sometimes, jeopardize the interest of whole populations. The virtue of justice being within the reach of the entire human community more than of single individuals, the final sentence in the definition proposed by Giuseppe Lippi and Mario Plebani, should therefore, in our view, be rewritten, less selfishly, for example like this: "For a given investment, these measurements are preferably made when they bring as much beneficence, and non-maleficence, as possible to the whole population".